Axillary artery injury in low-energy shoulder injury - Mannová, Zuzana; Křivohlávek, Martin; Šrám, Jaroslav (Úrazová chirurgie, 2020)
In the presented case reports, the author describes a rare complication in the dislocation and fracture of the proximal humerus. Both with the occurrence of a low-energy injury (simple fall). In the subsequent discussion, he deals with possible aetiology and mechanisms of a. axillaris injuries and its therapies.
Keywords: senioři; tomografie spirální počítačová; humerus; fraktury proximálního humeru; Shoulder Fractures; duplexní dopplerovská ultrasonografie; angiografie; Radiography; Pentoxifylline; luxace ramenního kloubu; Axillary Artery; Shoulder Dislocation; Angioplasty; Heparin; poranění cév; uzavřená repozice fraktury; Tomography, Spiral Computed; Humerus; Ultrasonography, Doppler, Duplex; Orthotic Devices; ženské pohlaví; Angiography; radiografie; Humans; Aspirin; arteria axillaris; protetické prostředky; pentoxifylin; Closed Fracture Reduction; heparin; Vascular System Injuries; Female; Aged; Conservative Treatment; angioplastika; úrazy pádem; Accidental Falls; lidé; konzervativní terapie